Business Strategy SME Wingko Loe Lan Ing After Pandemic in Lamongan, East Java Indonesia - Sarisda, Labiba Qonita; Hayati, Mardiyah (Universitas Muhammadiyah Jakarta, 2024)
SME Wingko Loe Lan Ing is a typical souvenir food establishment, or Wingko, located in the Babat District. The research's goal is to identify, analyze, and build a new business model for SMEs, such as Loe Lan Ing, to compete using the Business Model Canvas (BMC) and SWOT analysis. This research is required to assess Wingko Loe Lan Ing SME's business position using SWOT analysis and then develop it using the Business Model Canvas. According to the study's findings, Loe Lan Ing SMEs are in quadrant one, or an aggressive expansion plan, and have an alternative strategy for the new Business Model Canvas (BMC) proposal, which includes eight pieces for offering a new approach, such as the segment customer block there need to be additional consumers from outside the region, adding value to increase consumer trust and adding flavor variants, adding channels such as marketplaces on LAZADA and Bukalapak, dropship sales systems, catering and events businesses, adding key partners such as event organizers and food bloggers, main activity optimization with technology, main resources for website creation and the addition of silica gel to packaging, revenue streams that get additional income from the sale of production waste and event organizers, and the cost structure that requires spending for endorsements to food bloggers.